Understanding the CSR Awareness of Large Construction Enterprises in China. (26th November 2020) - Xie, Linlin; Xu, Ting; Le, Yun; Chen, Qing; Xia, Bo; Skitmore, Martin
Abstract : With the rapid growth of the construction industry in China in recent years, its impact on society and the environment is increasing, as well as the importance of corporate social responsibility (CSR). In order to understand the CSR awareness and CSR practices of Chinese domestic construction enterprises, this study conducted a comprehensive content analysis of the CSR reports of China's leading 100 domestic construction enterprises. The results show that the Chinese construction industry's CSR awareness is generally poor and CRS practices mainly involve corporate governance, environmental management, occupational health and development, economic responsibility, community development, and overseas responsibility. State-owned enterprises are more concerned with community responsibility, while private enterprises pay more attention to economic and employee development. These findings not only reveal the CSR awareness and CSR practices of Chinese domestic construction enterprises but also provide practical implications for construction enterprises in other countries to integrate CSR into their corporate governance system and strengthen their CSR practices.